Actinomadura apis sp. nov., isolated from a honey bee (Apis mellifera) hive, and the reclassification of Actinomadura cremea subsp. rifamycini Gauze et al. 1987 as Actinomadura rifamycini (Gauze et al.1987) sp. nov., comb. nov - Yaowanoot Promnuan (2018)
A Gram-reaction-positive aerobic actinomycete, designated strain IM17-1 T, was isolated from a honey bee (Apis mellifera) hive in Chiang Mai Province, Thailand. The strain formed a branched substrate mycelium and mature aerial mycelium bore short chains of arthrospores with warty surfaces. The cell wall contained meso-2,6-diaminopimelic acid (cell-wall type III) and the whole cell sugars were fucose, galactose, glucose, madurose, mannose and ribose. The major isoprenoid quinone was hexahydrogenated menaquinone with nine isoprene units and the predominant cellular fatty acids were C 16: 0 (33.8%), C 18: 1ω9c (32.7%), summed feature 3 (C 16: 1ω7c and/or iso-C 15: 0 2-OH) (8.7%) and 10-methyl C 18: 0 (8.2%). The phospholipids were diphosphatidylglycerol, phosphatidylinositol and phosphatidylinositol mannosides. These morphological and chemotaxonomic characteristics were consistent with the classification of IM17-1 T within the genus Actinomadura. Based on 16S rRNA gene sequence analysis, strain IM17-1 T was closely related to the type strains of Actinomadura cremea subsp. cremea (98.1%) and Actinomadura cremea subsp. rifamycini (98.6%); however, it represented a distinct phylogenetic lineage from the other species within this genus. The unique genetic characteristics were reaffirmed by low levels of DNA-DNA relatedness between strain IM17-1 T and the two most closely related type strains, A. cremea subsp. cremea JCM 3308T (56.5±4.9%) and A. cremea subsp. rifamycini JCM 3309T (31.0±22.6%), and further supported the proposal of IM17-1 T as a novel species. Strain IM17-1T (5JCM 16576T 5TISTR 1980T) thus represents a novel species of the genus Actinomadura, for which the name Actinomadura apis sp. nov. is proposed. In addition, the genotypic and phenotypic data suggested the reclassification of Actinomadura cremea subsp. rifamycini Gauze et al. 1987 as a separate species, Actinomadura rifamycini sp. nov., comb. nov. © 2011 IUMS.